Efektifitas Konseling Kelompok dalam Mengatasi Kecemasan Menghadapi Ujian pada Siswa - Harahap, Jumli Sabrial; Silvianetri, Silvianetri (Institut Agama Islam Negeri Curup, 2024)
This research aims to collect previous research which focuses on group counseling and student anxiety in facing exams. Student anxiety when facing exams is a complex problem. Apart from the problem of student anxiety at school, other problems can also concern the environment around students. Regarding this problem, it is necessary to implement group counseling by guidance and counseling teachers to avoid cases of student anxiety when facing exams. Generally, student anxiety in facing exams occurs due to two factors, namely internal and external factors. Where internal factors come from the student, while external factors come from outside the student, such as the family environment, society and the student's relationships. This research aims to review several research articles examining the effectiveness of group counseling to reduce student anxiety when taking exams. The method used in this research is a literature review indexed by Sinta. Which aims to collect, analyze and seek general views about the effectiveness of group counseling in reducing students' anxiety when facing exams at school. The research results showed that the seven articles analyzed with a focus on discussing group counseling gave positive results and revealed that group counseling using various approaches was effective in reducing students' anxiety when facing exams. It is hoped that the results of this research can be utilized by guidance and counseling teachers and future researchers.